PERAN GURU DALAM PERAN GURU DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA DI SDN 9 KWANDANGKABUPATEN GORONTALO UTARA MENINGKATKAN MOTIVASI BELAJAR SISWA DI SDN 9 KWANDANGKABUPATEN GORONTALO UTARA - Ritonga, Debi Borru; Pomalingo, Samsi; Halidu, Salma (SINERGI : Jurnal Riset Ilmiah, 2025)
This study aims to identify the role of teachers in enhancing student learning motivation at SDN 9 Kwandang, Gorontalo Utara Regency. Teachers are responsible not only for delivering lesson material but also for building students' character and motivation. The research method used is qualitative with a descriptive approach, involving observation, interviews, and documentation. The results show that teachers at SDN 9 Kwandang play a crucial role in creating a positive learning environment through creative and interactive teaching methods. They also provide emotional and academic support to students and relate lesson material to students' everyday lives to enhance the relevance of learning. The involvement of parents in the educational process is also identified as an important factor influencing students' learning motivation. These findings indicate that by understanding and applying appropriate strategies, teachers can significantly enhance students' learning motivation, which in turn contributes to better academic achievement.